Histomorphometric Comparative Analysis between Oral Dysplastic Potentially Malignant Disorders and Oral Squamous Cell Carcinoma - Pereira, Natalia Da Silva; Pinheiro, Tiago Novaes (European Journal of Dentistry, 2019)
Objective This study aimed to determine the correlation between the vascular mast cells and inflammatory changes in the potentially malignant disorders, compared to the oral squamous cell carcinoma (OSCC) in varying degrees of dysplasia.Materials and Methods Thirty samples were selected: 10 of OSCC, 10 of oral leukoplakia, and 10 of actinic keratosis. The toluidine blue technique was used on the mast cells, and hematoxylin and eosin were used for analyzing the lymphocytes, mitosis, and vessels. The quantification was performed using the ImageJ software after obtaining the images by light microscopy with a × 40 objective. Analysis of variance with p < 0.05 was considered for statistical significance.Results Mast cells (p < 0.0158), vessels (p < 0.9431), lymphocytes (p < 0.0001), and mitoses (p < 0.0009) were found in OSCC. In potentially malignant disorders, a lower density of these structures and a higher concentration of mitosis in the actinic keratosis were observed.Conclusion The results showed evidence of a positive correlation between mast cells and vascularization in the OSCC, suggesting the aggression of the disease. Intense inflammatory infiltrate indicates that other molecular events are involved in the carcinogenesis process, and further studies are necessary for a better understanding of it.
Keywords: carcinogenesis; lymphocytes; mast cells; mitosis; vascularization